The Influence Of Fiscal Policy On Economic Growth - Mas Andini (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The correlation between fiscal policy and economic growth has garnered significant interest recently. The economic expansion witnessed by various countries in recent decades has led to the emergence of a substantial body of theoretical and empirical literature aimed at elucidating these phenomena. There is a valid argument that can be made regarding the reciprocal relationship between economic growth and fiscal policy. This study examines the research undertaken on fiscal policies and their impact on economic growth. It is important to note that fiscal policy encompasses three main tools: government expenditure, taxation, and debt. Moreover, based on prior research, the correlation between fiscal policy and economic growth is ambiguous and inconsistent, with instances of both positive and negative associations. This study will examine the concept of fiscal policies, economic growth, and the correlation between these two factors based on prior research.